2020
DOI: 10.1017/s1368980020001123
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian immigrant fathers’ perspectives on child’s eating and feeding practices: a qualitative study conducted in the United States

Abstract: Objectives: Brazilians comprise a rapidly growing immigrant Latino group in the USA, yet little research has focused on health issues affecting Brazilian children in immigrant families. As increasing evidence is documenting fathers’ influential role in their children’s eating behaviours and ultimately weight status, the current study sought to explore the Brazilian immigrant fathers’ perspectives and practices related to child’s feeding practices and their preschool-aged children’s eating. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 76 publications
(163 reference statements)
0
8
0
Order By: Relevance
“…The common approach was to focus on a single category of caregivers. Eight studies focused exclusively on fathers [ 26 , 37 , 40 , 45 , 48 , 50 , 54 ]. Five studies focused exclusively on grandparents [ 33 , 38 , 42 , 44 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The common approach was to focus on a single category of caregivers. Eight studies focused exclusively on fathers [ 26 , 37 , 40 , 45 , 48 , 50 , 54 ]. Five studies focused exclusively on grandparents [ 33 , 38 , 42 , 44 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fathers’ body mass index and education level and child gender were not associated with perceived responsibility. Lindsay et al [ 48 ] found that Brazilian immigrant fathers perceived a greater role in feeding, relative to fathers in Brazil, since their immigrant status meant they had fewer people to help with child care in the U.S. They also found that fathers who had experienced food insecurity in the past perceived a greater role in feeding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Students start their research project by completing basic training in research ethics including foundational training in human subjects’ research with a focus on social–behavioral education. Examples of CER projects include mixed-methods research focused on (1) early childhood health promotion and obesity prevention and (2) human papillomavirus–associated cancer prevention (Lindsay, Delgado, et al, 2020; Lindsay, Greaney, et al, 2020; Lindsay, Moura Arruda, et al, 2020; Lindsay, Pineda, et al, 2020; Lindsay, Vianna, et al, 2020; Lindsay, Wallington, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%